Effectiveness of Bay Leaf Decoction (Syzygium polyanthum) on Reducing Blood Glucose Levels in Paok Motong, Masbagik, East Lombok - Kurniawan, Nadi; Rozikin; I Putu Bayu Agus Saputra; Sabariah; I Nyoman Bagus Aji Kresnapati (Current Biochemistry, 2023)
One disease that correlates with blood glucose levels is diabetes mellitus (DM). According to Basic Health Research (RISKESDAS), in Indonesia by 2030 there will be an increase of up to 21.3 million people suffering from diabetes mellitus. However, nowadays most people are afraid of the side effects of using the drugs they consume and are turning to herbal therapy to lower blood glucose levels. Bay leaves have the benefit of treating diabetes mellitus, hypercholesterolemia, hypertension, diarrhea and gastritis. Phytochemical analysis shows that bay leaves contain essential oils, tannins, flavonoids and terpenoids. The aim of the research was to determine the effect of bay leaf boiled water on reducing blood glucose levels. The research was an experimental One Group Pretest Post-test Design, namely the research subjects had their blood glucose levels measured before (pre-test) and after being given bay leaf boiled water (post-test). 41 respondents in Paok Motong Barat village, Masbagik District, East Lombok Regency had their Blood Glucose Levels (GDS) measured before (pre-test) and after (post-test) giving 300 mL of bay leaf boiled water. Paired Test Statistical Analysis was used to determine the difference in pretest and posttest blood glucose levels given bay leaf boiled water. The results of the study showed that there was a significant decrease in blood glucose levels (p= 0.001) by 15.22 mg/dL to 179.27 mg/dL before administering bay leaf decoction amounting to 194.49 mg/dL. The conclusion is that there is a significant effect (p=0.001) of giving boiled bay leaves on reducing blood glucose levels. The suggestion for this research is to increase the number of respondents in the research as well as examination variables such as fasting blood glucose